2021
DOI: 10.1021/acsaelm.1c00277
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromism Frequency-Selective Emitter for Infrared Stealth Application

Abstract: A thermochromism frequency-selective emitter (TFSE) capable of both emissivity modulation and radiative cooling is presented. The emitter integrates a metallic resonating component and the phase change material of vanadium dioxide (VO 2 ). In the atmospheric windows of 3−5 and 8−14 μm wave bands, the emissivity of the TFSE varies from 0.41 to 0.11 as the phase transition of VO 2 from the insulating to metallic phase takes place. In the atmospheric absorption band of 5−8 μm, the emitter can actively dissipate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…This particular form of emissivity is caused by the asynchronous phase transition temperature of the W-doped VO 2 layer and the VO 2 layer. Similarly, Zhao et al 291 proposed a new metal–dielectric–metal (MIM) structure, as shown in Fig. 31b.…”
Section: Smart Applications Of Element-doped Vo2mentioning
confidence: 99%
“…This particular form of emissivity is caused by the asynchronous phase transition temperature of the W-doped VO 2 layer and the VO 2 layer. Similarly, Zhao et al 291 proposed a new metal–dielectric–metal (MIM) structure, as shown in Fig. 31b.…”
Section: Smart Applications Of Element-doped Vo2mentioning
confidence: 99%
“…[ 1 ] However, due to the performance limits of conventional materials, various needs in building energy management, [ 2,3 ] packing technology, [ 4,5 ] safety, [ 6 ] and military applications [ 7 ] cannot be satisfied sufficiently, which leads to developing advanced materials having the engineered properties depending on their missions. [ 8 ] The camouflage platform with metamaterials to manipulate electromagnetic energy efficiently is one of the solutions to satisfy the needs in energy, [ 9,10 ] military, [ 11–15 ] and space applications. [ 16 ] Hence, many researchers have developed several camouflage platforms with metamaterials, [ 17,18 ] such as metal‐dielectric‐metal (MDM) structure, [ 19,20 ] photonic crystal, [ 21 ] multi‐layers, [ 22,23 ] and novel materials [ 24–27 ] to control the electromagnetic energy for breaking the limits of conventional applications.…”
Section: Introductionmentioning
confidence: 99%
“…
camouflage platform with metamaterials to manipulate electromagnetic energy efficiently is one of the solutions to satisfy the needs in energy, [9,10] military, [11][12][13][14][15] and space applications. [16] Hence, many researchers have developed several camouflage platforms with metamaterials, [17,18] such as metal-dielectric-metal (MDM) structure, [19,20] photonic crystal, [21] multilayers, [22,23] and novel materials [24][25][26][27] to control the electromagnetic energy for breaking the limits of conventional applications.
…”
mentioning
confidence: 99%
“…Vanadium dioxide (VO 2 ) is known as a functional material for smart windows, infrared stealth, imaging, data storage, memristors, tunable-frequency metamaterials, multifunctional sensors, , etc. It undergoes a reversible metal–insulator transition at ∼68 °C, which can be further lowered to room temperature by doping. Monoclinic VO 2 (M) is a low-temperature phase, which is a semiconductor and infrared-transparent, whereas high-temperature rutile VO 2 (R) is a metal phase with low near-infrared transition and low infrared radiation.…”
Section: Introductionmentioning
confidence: 99%
“…9−12 In photodetectors, hybridization of ZnO with a second semiconductor, e.g., perovskite, could achieve an ambipolar photoresponse, higher switching ratio, faster response speed, and higher response and detection rate than compared to corresponding monophase devices. 13−16 Vanadium dioxide (VO 2 ) is known as a functional material for smart windows, 17−20 infrared stealth, 21 imaging, 22 data storage, 23 memristors, 24 tunable-frequency metamaterials, 25 multifunctional sensors, 26,27 etc. It undergoes a reversible metal−insulator transition at ∼68 °C, which can be further lowered to room temperature by doping.…”
Section: Introductionmentioning
confidence: 99%